High-specific-surface-area porous carbon / sulfur composite material, preparation method and application thereof, and aqueous zinc-sulfur battery
By using the high-proprietary porous carbon/sulfur composite material as the positive electrode material of the zinc-sulfur battery of the water system, it solves the problem of the low discharge platform and capacity attenuation of cathode materials in existing technologies, and realizes the high ratio capacity and excellent electrochemical of the battery. performance.
Patent Information
- Application Number
- CN202411432651.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The cathode materials of existing aqueous zinc-sulfur batteries have problems with low discharge platform and rapid capacity decay, resulting in poor electrochemical performance and limiting the scalability and reliability of the battery.
A high specific surface area porous carbon/sulfur composite material is used as the cathode material. By uniformly mixing the biomass precursor and sulfate, carbonizing and pickling at high temperature, a three-dimensional carbon nanostructure with developed pore structure and mutual cross-linking is prepared. of composite materials.
It improves the ratio and magnification of the zinc-sulfur battery of the water-based zinc-sulfur battery, and shows excellent comprehensive electrochemical properties, including high voltage discharge platforms and low polarization voltage.
Smart Images

Figure CN119349574A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon materials, and in particular to a high specific surface area porous carbon / sulfur composite material, a preparation method and application thereof, and an aqueous zinc-sulfur battery. Background Art
[0002] As the proportion of renewable energy (such as solar and wind energy) in the global energy structure increases, the demand for large-scale energy storage systems is increasing, and effective energy storage technology is needed to address the challenges brought by its intermittent and unpredictable nature. Electrochemical energy storage systems play a key role in the conversion and storage of electrical energy. Among them, rechargeable batteries are one of the most important technologies in grid-scale energy storage, with advantages such as high flexibility and high-capacity storage. However, there are many types of rechargeable battery technologies. At present, traditional lithium-ion batteries (LIB S ) dominates the market, but has limitations in terms of energy density, cost, material scarcity, etc., and the use of organic solutions and overly active lithium metals can lead to safety issues, which hinder its practical application in GES and force the search for new storage solutions.
[0003] Aqueous batteries, especially aqueous zinc-ion batteries (AZMBs), are promising candidates due to their low cost (US$2.9 kg -1 ), high theoretical capacity (819mA hg -1 ) and compatibility with aqueous electrolytes, and its inherent safety and high capacity make it a substitute for lithium-ion batteries, which has attracted great research interest from researchers. Aqueous rechargeable zinc-ion batteries have become a promising safe and high-energy storage device. As an attractive material, zinc has been used in the early days of manganese-based, vanadium-based and organic-based cathodes as well as traditional Zn 2+ Insertion / deinsertion mechanism. Recently, conversion cathodes with multiple electron transfer have replaced traditional mechanisms and become a new research hotspot, thereby improving the capacity of aqueous rechargeable zinc-ion batteries.
[0004] Sulfur (S) is the most representative cathode for aqueous rechargeable Zn-ion batteries due to its high capacity (1675 mA h g -1 ) and a low cost of $0.25 / kg. Studies have shown that the energy density of aqueous zinc-sulfur primary batteries is 1083.3Wh kg -1 However, when used in rechargeable batteries, the primary cell has significant polarization and a low discharge plateau of 0.3 V, which is attributed to the slow kinetics of the sulfur electrode. The low discharge plateau is also reported in nickel-sulfur, copper-sulfur, and lead-sulfur batteries. In addition, the formation of passivated ZnS is another reason that hinders practical use.
[0005] At present, remarkable achievements have been made in improving the electrochemical performance and stability of anodes. However, due to the lack of high energy density and reversible cathode materials, the practical application of AZMBs (aqueous zinc-sulfur batteries) still faces many limitations, which affects its scalability and reliability. In existing studies, the positive electrode of aqueous zinc-sulfur batteries is usually composed of porous carbon materials and active material sublimated sulfur, and the sulfur positive electrode is prepared by the traditional melt diffusion method. However, due to the high viscosity of molten sulfur, it is difficult to penetrate into the micropores and mesopores, which often leads to the clogging of the pores of the carbon support, making the specific surface area of the final positive electrode material much lower than the high specific surface area of the original support material. The low specific surface area means that the electrode-electrolyte interface is insufficient, resulting in slow electrode kinetics. On the other hand, although the conversion sulfur cathode has the potential to provide high capacity and maintain structural stability during cycling, in AZMBs, the reduction reaction of the sulfur cathode shows a low discharge platform of 0.3-0.47V. In addition, the capacity of the sulfur cathode decays rapidly during cycling, which further limits the performance of AZMBs. Compared with other metal-sulfur batteries, the higher binding energy of ZnS exacerbates the irreversible redox reactions in aqueous zinc-ion batteries. Various schemes have been developed to improve the sulfur conversion kinetics in AZMBs, including doping with redox catalysts or adding redox mediators to the electrolyte. Although current schemes have improved the electrochemical performance of aqueous zinc-sulfur batteries to varying degrees, the discharge voltage is still challenged by the low electrochemical potential of sulfur reduction.
[0006] Based on the defects of the current aqueous zinc-sulfur battery preparation and low discharge platform, it is necessary to improve this. Summary of the invention
[0007] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a high specific surface area porous carbon / sulfur composite material and its preparation method and application, and an aqueous zinc-sulfur battery, so as to solve or at least partially solve the above technical defects existing in the prior art.
[0008] In a first aspect, the present invention provides a method for preparing a porous carbon / sulfur composite material with a high specific surface area, comprising the following steps:
[0009] preparing carbon / sulfur composite precursors;
[0010] The carbon / sulfur composite material precursor is placed in a tube furnace, carbonized and acid-washed under an inert atmosphere to obtain a porous carbon / sulfur composite material with a high specific surface area;
[0011] The method for preparing the carbon / sulfur composite material precursor comprises the following steps:
[0012] washing and drying the biomass precursor to obtain a pretreated precursor;
[0013] The pretreated precursor and sulfate are mixed in proportion, and are initially ground and subsequently ball-milled to obtain the carbon / sulfur composite material precursor.
[0014] Furthermore, in the above technical solution, the specific steps of mixing the pre-treated precursor and the sulfate in proportion, and performing preliminary grinding and subsequent ball milling to make them uniform are as follows:
[0015] The pretreated precursor and sulfate are preliminarily ground in a mortar at a mass ratio of 1:0.5 to 1:3, and then the resulting mixture is placed in a ball mill for 0.5 to 12 hours; after the ball milling is completed, the mixture is dried, and the resulting uniformly dispersed material is a carbon / sulfur composite material precursor.
[0016] Specifically, the pretreatment precursor and the sulfate are in a mass ratio of 1:0.5 to 1:3. It should be noted that if the sulfate is too much, the carbon-sulfur composite material cannot be obtained and the yield is low; if the sulfate is too little, the activation effect is poor and the sulfur loading is small.
[0017] Preferably, in the above technical solution, the rotation speed of the ball mill is 60 to 360 r / min.
[0018] Furthermore, in the above technical solution, the biomass precursor includes but is not limited to jujube leaf powder, pine needle powder, turmeric powder, onion powder, etc.
[0019] Furthermore, in the above technical solution, the sulfate includes but is not limited to potassium sulfate, potassium persulfate, potassium thiosulfate, etc.
[0020] Furthermore, in the above technical solution, the specific steps of placing the carbon / sulfur composite material precursor in a tube furnace and carbonizing it under an inert atmosphere are:
[0021] The carbon / sulfur composite precursor is placed in a tube furnace, heated to 700-900°C at 3-7°C / min under an inert atmosphere, and maintained for 1-2 hours to obtain a porous carbon / sulfur composite with a high specific surface area. It should be noted that when the carbonization temperature is lower than 700°C or higher than 900°C, a porous carbon / sulfur composite with a high specific surface area cannot be prepared.
[0022] Furthermore, in the above technical solution, the inert gas includes but is not limited to argon, helium, nitrogen, etc.
[0023] Furthermore, in the above technical scheme, the carbonized product is pickled with 0.1-3 mol / L dilute hydrochloric acid or dilute sulfuric acid solution for 0.5-5 h, and then the product is repeatedly washed with deionized water and anhydrous ethanol for 3-5 times until the pH value of the solution after washing is neutral, and finally the product is dried at 65-80°C.
[0024] In a second aspect, the present invention further provides a high specific surface area porous carbon / sulfur composite material, which is prepared by the above-mentioned preparation method of the high specific surface area porous carbon / sulfur composite material.
[0025] In a third aspect, the present invention also provides an application of a porous carbon / sulfur composite material with a high specific surface area prepared by the preparation method as an electrode material for an aqueous zinc-sulfur battery.
[0026] In a fourth aspect, the present invention further provides an aqueous zinc-sulfur battery, comprising: a positive electrode, a negative electrode, an electrolyte and a separator;
[0027] Wherein, the positive electrode comprises the high specific surface area porous carbon / sulfur composite material mentioned above.
[0028] The roles played by each raw material used in the present invention are as follows:
[0029] In the in-situ loading method, biomass is mainly responsible for providing precursors, and potassium sulfate mainly plays the role of activation and pore formation, so that the product has a higher specific surface area and pore volume.
[0030] The high specific surface area porous carbon / sulfur composite material, preparation method and application thereof, and aqueous zinc-sulfur battery of the present invention have the following beneficial effects compared with the prior art:
[0031] (1) The method for preparing the high specific surface area porous carbon / sulfur composite material of the present invention does not use a hard template, an additional activator, or an additional sulfur source for secondary loading. Sulfate is directly used as a sulfur source, uniformly mixed with a pretreated biomass precursor at room temperature, activated by sulfate at high temperature, and grown by in-situ loading to obtain a three-dimensional porous carbon / sulfur composite material. After hydrochloric acid pickling, a high sulfur content carbon / sulfur composite material can be obtained, and its electrochemical and kinetic properties are significantly better than those previously reported. Thanks to the highly uniform composite material, the cross-linked three-dimensional carbon nanostructure, and the developed specific surface area, the obtained porous carbon material exhibits excellent electrochemical properties as a positive electrode material for aqueous zinc-sulfur batteries.
[0032] (2) The aqueous zinc-sulfur battery of the present invention uses a high specific surface area porous carbon / sulfur composite material as the positive electrode. Since the high specific surface area porous carbon / sulfur composite material has a developed pore structure and a mutually cross-linked three-dimensional carbon nanostructure, the high specific surface area porous carbon / sulfur composite material is used as the positive electrode material, so that the aqueous zinc-sulfur battery has a high specific capacity and excellent rate performance, and exhibits excellent comprehensive electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 The XRD spectrum of the porous carbon / sulfur composite material with high specific surface area prepared in Example 1 of the present invention;
[0035] Figure 2 (a)-(b) and (c)-(e) are respectively the SEM morphologies and mapping graphs of the high specific surface area porous carbon / sulfur composite material prepared in Example 1 of the present invention;
[0036] Figure 3 This is the N2 adsorption and desorption thermodynamic curve of the high specific surface area porous carbon / sulfur composite material prepared in Example 1 of the present invention;
[0037] Figure 4 The constant current charge-discharge curve of the aqueous zinc-sulfur battery assembled in Application Example 1 of the present invention at a current density of 0.5 A / g;
[0038] Figure 5 The constant current charge-discharge curve of the aqueous zinc-sulfur battery assembled in Application Example 2 of the present invention at a current density of 0.5 A / g;
[0039] Figure 6 The constant current charge-discharge curve of the aqueous zinc-sulfur battery assembled in Application Example 3 of the present invention at a current density of 0.5 A / g;
[0040] Figure 7 The constant current charge-discharge curve of the aqueous zinc-sulfur battery assembled in Application Example 4 of the present invention at a current density of 0.5 A / g;
[0041] Figure 8 This is a constant current charge-discharge curve of the aqueous zinc-sulfur battery assembled in Application Example 5 of the present invention at a current density of 0.5 A / g;
[0042] Fig. 9 For comparison, the aqueous zinc-sulfur battery obtained in Example 1 was -1 Constant current charge and discharge curves at current density. DETAILED DESCRIPTION
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The present invention provides a method for preparing a porous carbon / sulfur composite material with a high specific surface area, comprising the following steps:
[0045] S1. preparing a carbon / sulfur composite material precursor;
[0046] S2, placing the carbon / sulfur composite material precursor in a tube furnace, carbonizing and acid washing under an inert atmosphere to obtain a porous carbon / sulfur composite material with a high specific surface area;
[0047] The method for preparing the carbon / sulfur composite material precursor comprises the following steps:
[0048] S11, washing and drying the biomass precursors such as jujube leaf powder to obtain a pretreated precursor;
[0049] S12, grinding the pretreated precursor and sulfate in proportion and ball-milling them to obtain a carbon / sulfur composite material precursor.
[0050] It should be noted that the preparation method of the porous carbon / sulfur composite material with high specific surface area provided in the embodiment of the present application does not use a hard template, an additional activator and an additional sulfur source for secondary loading, but uses sulfate directly as a sulfur source, uniformly mixes with a pretreated precursor at room temperature, is activated by sulfate at high temperature, and is grown by in-situ loading to obtain a three-dimensional porous carbon / sulfur composite material, and a carbon / sulfur composite material with a high sulfur content can be obtained by acid washing, and its electrochemical and kinetic properties are significantly better than those previously reported. Thanks to the highly uniform composite material, the cross-linked three-dimensional carbon nanostructure and the developed specific surface area, the obtained porous carbon material exhibits excellent electrochemical properties as a positive electrode material for aqueous zinc-sulfur batteries.
[0051] In a preferred embodiment of the present invention, a carbon / sulfur composite material precursor is placed in a tubular furnace, heated to 700-900°C at 3-7°C / min under an inert atmosphere, and maintained for 1-2h to obtain a high specific surface area porous carbon / sulfur composite material.
[0052] Specifically, the inert gas includes but is not limited to argon, helium, nitrogen and the like.
[0053] In some embodiments, the preparation method of the carbon / sulfur composite material precursor also includes the following steps: preliminarily grinding the pretreated precursor and sulfate in a mortar at a ratio of 1:0.5 to 1:3, then placing the material in a ball mill for 0.5 to 12 hours, maintaining a forward and reverse rotation speed of 60 to 360 r / min, and drying at 65 to 85°C after grinding to obtain a uniformly dispersed material, which is a carbon / sulfur composite material precursor.
[0054] In some embodiments, the carbonized product is pickled with 0.1-3 mol / L dilute hydrochloric acid or dilute sulfuric acid solution for 0.5-5 h, and the product is repeatedly washed with deionized water and anhydrous ethanol for 3-5 times until the pH value of the solution after washing is neutral, and the product is dried at 65-80° C. to evaporate the water.
[0055] In a preferred embodiment of the present invention, the concentration of the dilute hydrochloric acid or dilute sulfuric acid solution is 0.5-2 mol / L.
[0056] In some embodiments, a method for preparing a porous carbon / sulfur composite material with a high specific surface area, the biomass precursor includes but is not limited to jujube leaves, pine needle powder, turmeric powder, onion powder, etc.;
[0057] The sulfate includes but is not limited to potassium sulfate, potassium persulfate, potassium thiosulfate and the like.
[0058] Based on the same inventive concept, the embodiment of the present application also provides an aqueous zinc-sulfur battery, including: a positive electrode, a negative electrode, an electrolyte and a separator;
[0059] Wherein, the positive electrode comprises the high specific surface area porous carbon / sulfur composite material prepared as above.
[0060] The negative electrode is a zinc sheet;
[0061] The electrolyte is 1-3 mol / L zinc sulfate aqueous solution + 0.06 mol / L zinc iodide additive;
[0062] The diaphragm is glass fiber filter paper.
[0063] Specifically, the positive electrode is composed of a high specific surface area porous carbon / sulfur composite material and conductive carbon black, and a binder are mixed in alcohol in a mass ratio of 8:1:1, made into a slurry, coated on a stainless steel current collector, and dried at 80 degrees Celsius as the positive electrode; wherein the binder is PVDF.
[0064] Specifically, the positive electrode of the aqueous zinc-sulfur battery of the present application includes a high specific surface area porous carbon / sulfur composite material. Since the high specific surface area porous carbon / sulfur composite material has a highly uniform, mutually cross-linked three-dimensional carbon nanostructure and a developed specific surface area, the obtained porous carbon material exhibits excellent electrochemical properties as a positive electrode material of the aqueous zinc-sulfur battery.
[0065] The following further describes the method for preparing the porous carbon / sulfur composite material of the present application with specific examples.
[0066] Example 1
[0067] The present invention provides a method for preparing a porous carbon / sulfur composite material with a high specific surface area, comprising the following steps:
[0068] S1. Wash and dry the jujube leaf powder to obtain pretreated jujube leaf powder; grind 6g of the pretreated jujube leaf powder and 6g of potassium sulfate in a mortar at a mass ratio of 1:1, and then place the resulting mixture in a ball mill for 0.5 to 12 hours, with the rotation speed maintained at 60 to 360 rpm. After grinding and drying, a uniformly dispersed material is obtained, which is a carbon / sulfur composite material precursor.
[0069] S2, placing the carbon / sulfur composite material precursor in a tube furnace, heating it to 800° C. at 5° C. / min under an argon atmosphere, and maintaining it for 2 hours to obtain a porous carbon / sulfur composite material with a high specific surface area;
[0070] S3. The carbonized product is acid-washed with a 2 mol / L dilute hydrochloric acid solution for 2 h, and the acid-washed product is repeatedly filtered and washed with deionized water and anhydrous ethanol for 3 to 5 times until the pH value of the solution after washing is neutral. The product is dried at 85 to 95°C to evaporate the water.
[0071] Example 2
[0072] The method for preparing a porous carbon / sulfur composite material with a high specific surface area in this embodiment is basically the same as that in Example 1, except that the carbonization temperature in step S2 of this embodiment is 700° C., and the other processes are the same.
[0073] Example 3
[0074] The method for preparing a porous carbon / sulfur composite material with a high specific surface area in this embodiment is basically the same as that in Example 1, except that the carbonization temperature in step S2 of this embodiment is 900° C., and the other processes are the same.
[0075] Example 4
[0076] The preparation method of a carbon / sulfur composite material in this embodiment is basically the same as that in Example 1, the only difference is that the mass ratio of the pretreated jujube leaf powder to potassium sulfate in step S1 of this embodiment is 1:0.5, and the other processes are the same.
[0077] Example 5
[0078] The preparation method of a carbon / sulfur composite material in this embodiment is basically the same as that in Example 1, the only difference is that the mass ratio of the pretreated jujube leaf powder to potassium sulfate in step S1 of this embodiment is 1:3, and the other processes are the same.
[0079] Comparative Example 1
[0080] This comparative example is a carbon / sulfur composite material prepared by a traditional melt diffusion method, and the specific steps are as follows: commercial Ketjen black carbon and sublimated sulfur are ground in an agate mortar at a mass ratio of 1:1 for 40 minutes to ensure that the sulfur loading of the comparative sample is consistent with that of the experimental group. Then, the mixture is placed in a stainless steel reactor and heated to 160°C in a muffle furnace at a heating rate of 2°C / min, kept warm for two hours, and cooled to room temperature after the reaction is completed to obtain the carbon / sulfur composite material.
[0081] Application Example 1
[0082] This application embodiment provides an aqueous zinc-sulfur battery, including: a positive electrode, a negative electrode, an electrolyte and a separator;
[0083] The preparation method of the positive electrode is as follows: the high specific surface area porous carbon / sulfur composite material prepared in Example 1, conductive carbon black, and a binder are mixed in alcohol at a mass ratio of 8:1:1 to make a slurry, which is applied on a stainless steel current collector and dried at 80 degrees Celsius as the positive electrode; wherein the binder is PVDF;
[0084] The negative electrode is a zinc sheet;
[0085] The electrolyte is 3 mol / L zinc sulfate aqueous solution + 0.06 mol / L zinc iodide additive;
[0086] The diaphragm is glass fiber filter paper.
[0087] Application Example 2
[0088] This application example provides an aqueous zinc-sulfur battery, whose structure is basically the same as that of application example 1, with the only difference being that in the preparation method of the positive electrode of this application example, the high specific surface area porous carbon / sulfur composite material prepared in example 2 is used as the active material, and its dosage and other processes are the same.
[0089] Application Example 3
[0090] This application example provides an aqueous zinc-sulfur battery, whose structure is basically the same as that of application example 1, with the only difference being that in the preparation method of the positive electrode of this application example, the high specific surface area porous carbon / sulfur composite material prepared in example 3 is used as the active material, and its dosage and other processes are the same.
[0091] Application Example 4
[0092] This application example provides an aqueous zinc-sulfur battery, whose structure is basically the same as that of application example 1, with the only difference being that in the preparation method of the positive electrode of this application example, the carbon / sulfur composite material prepared in example 4 is used as the active material, and its dosage and other processes are the same.
[0093] Application Example 5
[0094] This application example provides an aqueous zinc-sulfur battery, whose structure is basically the same as that of application example 1, with the only difference being that in the preparation method of the positive electrode of this application example, the carbon / sulfur composite material prepared in example 5 is used as the active material, and its dosage and other processes are the same.
[0095] Comparative application example 1
[0096] This comparative application example provides an aqueous zinc-sulfur battery, whose structure is basically the same as that of application example 1, with the only difference being that in the preparation method of the positive electrode of this application example, the carbon / sulfur composite material prepared in comparative example 1 is used as the active material, and its dosage and other processes are the same.
[0097] Performance Testing
[0098] The XRD spectrum of the porous carbon / sulfur composite material prepared in Example 1 of the present application is as follows Figure 1 shown.
[0099] from Figure 1 It can be seen that a gentle broad peak appears at about 23°, which belongs to the (002) crystal plane of amorphous carbon.
[0100] The SEM morphology and mapping of the carbon / sulfur composite material prepared in Example 1 of the present application are as follows: Figure 2 As shown. Figure 2 It can be seen that a high content of sulfur was successfully introduced into the porous carbon, and the four elements of carbon, nitrogen, oxygen and sulfur were evenly distributed in the prepared porous carbon / sulfur composite material.
[0101] The N2 adsorption and desorption thermodynamic curve of the carbon-sulfur composite material prepared in Example 1 of the present application was tested, and the results were as follows: Figure 3 Specifically, the N2 adsorption and desorption thermodynamic curve was tested using the American ASAP-2460 specific surface area and pore size analyzer.
[0102] from Figure 3 It can be seen that the adsorption-desorption curve of the porous carbon / sulfur composite material prepared in Example 1 has an obvious hysteresis loop, indicating that there are a large number of mesopores inside the porous carbon. The final test results show that the specific surface area of the obtained carbon nanosheet is 494.3m 2 g-1 .
[0103] The electrochemical performance of the aqueous zinc-sulfur battery assembled in Example 1 was tested using a CHI-660 electrochemical workstation. -1 The constant current charge and discharge curve under the current density is as follows Figure 4 As shown. Figure 4 It can be seen that the maximum mass specific capacity of aqueous zinc-sulfur batteries is 1493.4 mAh g -1 , and exhibited a high voltage discharge platform of 0.71V and a polarization voltage of 0.42V.
[0104] Figure 5 and Figure 6 The materials prepared at different carbonization temperatures are 0.5Ag -1 Constant current charge and discharge curves at current density.
[0105] in: Figure 5 The aqueous zinc-sulfur battery assembled in Example 2 of the present invention is 0.5Ag -1 Constant current charge and discharge curves at a current density of 1.280 mAh g / cm2. As can be seen from the figure, after carbonization at 700 °C, the assembled battery exhibits a charge and discharge capacity of 1247 mAh g / cm2. -1 Specific capacity, 0.5V discharge platform and 0.64V polarization voltage.
[0106] Figure 6 The aqueous zinc-sulfur battery assembled in Example 3 of the present invention is 0.5A g -1 Constant current charge and discharge curves at a current density of 1.38 Å; as can be seen from the figure, after carbonization at 900 °C, the assembled battery exhibits a charge and discharge capacity of 1204 mAh g -1 Specific capacity, discharge platform of 0.51V and polarization voltage of 0.63V.
[0107] Figure 7 and Figure 8 The materials prepared under different proportions are 0.5Ag -1 Constant current charge and discharge curves at current density.
[0108] in: Figure 7 The aqueous zinc-sulfur battery assembled in Example 4 of the present invention is 0.5Ag -1 Constant current charge and discharge curves at a current density of 100 mAh g -1 Specific capacity, 0.49V discharge platform and 0.65V polarization voltage.
[0109] Figure 8The aqueous zinc-sulfur battery assembled in Example 5 of the present invention is 0.5A g -1 Constant current charge and discharge curves at a current density of 1.30 MW; as can be seen from the figure, when the ratio of biomass carbon precursor to potassium sulfate is 1:3, the assembled battery exhibits a charge and discharge capacity of 1161 mAh g -1 Specific capacity, 0.5V discharge platform and 0.64V polarization voltage.
[0110] Fig. 9 For comparison, the aqueous zinc-sulfur battery obtained in Example 1 was -1 The constant current charge and discharge curve under the current density of 1200mAh g -1 Specific capacity, 0.4V discharge platform and 0.8V polarization voltage.
[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous carbon / sulfur composite material with a high specific surface area, characterized in that: The following steps are involved: preparing carbon / sulfur composite precursors; The carbon / sulfur composite material precursor is placed in a tube furnace, carbonized and acid-washed under an inert atmosphere to obtain a porous carbon / sulfur composite material with a high specific surface area; The method for preparing the carbon / sulfur composite material precursor comprises the following steps: washing and drying the biomass precursor to obtain a pretreated precursor; The pretreated precursor and sulfate are mixed in proportion, and are initially ground and subsequently ball-milled to obtain the carbon / sulfur composite material precursor.
2. The preparation method according to claim 1, characterized in that: The specific steps of mixing the pre-treated precursor and sulfate in proportion, and then subjecting them to preliminary grinding and subsequent ball milling to uniformity are as follows: The pretreated precursor and sulfate are preliminarily ground in a mortar at a mass ratio of 1:0.5 to 1:3, and then the resulting mixture is placed in a ball mill for 0.5 to 12 hours; after the ball milling is completed, the mixture is dried, and the resulting uniformly dispersed material is a carbon / sulfur composite material precursor.
3. The preparation method according to claim 1, characterized in that: The biomass precursors include but are not limited to jujube leaf powder, pine needle powder, turmeric powder, and onion powder.
4. The preparation method according to claim 1, characterized in that: The sulfate includes but is not limited to potassium sulfate, potassium persulfate, and potassium thiosulfate.
5. The preparation method according to claim 1, characterized in that: The specific steps of carbonizing the carbon / sulfur composite precursor in a tube furnace under an inert atmosphere are as follows: The carbon / sulfur composite material precursor is placed in a tube furnace, heated to 700-900° C. at 3-7° C. / min under an inert atmosphere, and maintained for 1-2 hours to obtain a porous carbon / sulfur composite material with a high specific surface area.
6. The preparation method according to claim 1, characterized in that: The carbonized product is pickled with 0.1-3 mol / L dilute hydrochloric acid or dilute sulfuric acid solution for 0.5-5 h, and then repeatedly washed with deionized water and anhydrous ethanol for 3-5 times until the pH value of the solution after washing is neutral, and finally the product is dried at 65-80 ° C.
7. A porous carbon / sulfur composite material with a high specific surface area prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the high specific surface area porous carbon / sulfur composite material prepared by the preparation method according to any one of claims 1 to 6 as an electrode material for aqueous zinc-sulfur batteries.
9. An aqueous zinc-sulfur battery, comprising: Positive electrode, negative electrode, electrolyte and separator; characterized in that: The positive electrode comprises a porous carbon / sulfur composite material with a high specific surface area prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Zinc ion battery
CN102324579A
Lithium-sulfur battery sulfur / carbon composite positive electrode material, preparation method and applications thereof
CN103236560A
Preparation method of high purity porous carbon
CN108128774A
Micro-nano porous carbon-loaded sulfur composite material prepared by egg white carbonization and preparation method and application thereof
CN110350176A
Heteroatom-doped porous carbon material as well as preparation method and application thereof
CN113942995A